2012
DOI: 10.1159/000338732
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intravitreal Bevacizumab Upload Followed by a Dexamethasone Implant versus Dexamethasone Implant Monotherapy for Retinal Vein Occlusion with Macular Edema

Abstract: Purpose: To compare the efficacy and safety of three intravitreal bevacizumab upload injections followed by a dexamethasone implant versus dexamethasone implant monotherapy in eyes with macular edema due to retinal vein occlusion. Methods: Sixty-four eyes of 64 patients were included in this prospective, consecutive, nonrandomized case series: group 1 consisted of 38 patients (22 with central retinal vein occlusion, CRVO, 16 with branch retinal vein occlusion, BRVO) treated using a dexamethasone implant (Ozurd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
2
21
0
1
Order By: Relevance
“…The novel DDS applicator is a well-established applicator system to apply sustained release of DEX-implants into the vitreous cavity. With favorable confidence in intravitreal DEX injections (17,18,19) among treating physicians, the sharper novel DDS needle will increase in use as confirmed by our measurements in this experimental study.…”
Section: Dds Applicatorsupporting
confidence: 65%
“…The novel DDS applicator is a well-established applicator system to apply sustained release of DEX-implants into the vitreous cavity. With favorable confidence in intravitreal DEX injections (17,18,19) among treating physicians, the sharper novel DDS needle will increase in use as confirmed by our measurements in this experimental study.…”
Section: Dds Applicatorsupporting
confidence: 65%
“…Byun et al [ 183 ], in a study of 134 consecutive patients that were treated with either intravitreal triamcinolone or intravitreal bevacizumab for macular edema caused by BRVO, found that both were equally effective for improving visual acuity; however, the intravitreal triamcinolone group showed a longer mean duration of improvement and less disease recurrence and required fewer injections. Mayer et al [ 184 ] reported that in BRVO, dexamethasone implant monotherapy was associated with better functional outcome than intravitreal bevacizumab upload followed by a dexamethasone implant. Kwon et al [ 178 ], on a review of medical records of the patients treated with intravitreal triamcinolone with macular edema secondary to BRVO, found that the natural history was the same as that from this treatment at 12 months.…”
Section: Intravitreal Corticosteroid Therapymentioning
confidence: 99%
“…[5][6][7][8][9] We previously described the response to a pharmacological treatment of macular edema associated with RVO using the present treatment strategy with an Ozurdex monotherapy as a first-line treatment regime compared with an anti-VEGF-loading dose using three bevacizumab injections followed by a dexamethasone implant. 10 However, with regard to the potential side effects of a long-term treatment using dexamethasone, such as a raise of intraocular pressure and cataract formation, we feel the importance to report on the safety and efficacy over a 12-month follow-up of our patients.…”
Section: Introductionmentioning
confidence: 99%